EFFECTIVE TEACHING THE PARTS OF SPEECH IN A SIMPLE SENTENCE - Khairani , Miftahul (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2019)
This articles argue that English Teachers should know all parts ofspeech. The research methodology is content analysis. The findings of researchare before making sentences; English teachers must make a sense of thestructure of a sentence. There are three major properties of sentence structure:Linearity, Hierarchy, Categorically. The structure of simple sentences basicallypatterned as Subject-Verb-Object (SVO). A sentence must be containing someparts of speech. Some parts of speech in the sentence could be shifted but itsimpact in the different meaning of sentences. In English, object can shift thesubject but the meaning of the first sentence would be change. The sentencewould have the same meaning though object and subject shift just in the passiveform.